Fingerprinting stress: Stylolite and calcite twinning paleopiezometry revealing the complexity of progressive stress patterns during folding—The case of the Monte Nero anticline in the Apennines, Italy. Issue 7 (19th July 2016) - Beaudoin, Nicolas; Koehn, Daniel; Lacombe, Olivier; Lecouty, Alexandre; Billi, Andrea; Aharonov, Einat; Parlangeau, Camille
Abstract: In this study we show for the first time how quantitative stress estimates can be derived by combining calcite twinning and stylolite roughness stress fingerprinting techniques in a fold‐and‐thrust belt. First, we present a new method that gives access to stress inversion using tectonic stylolites without access to the stylolite surface and compare results with calcite twin inversion. Second, we use our new approach to present a high‐resolution deformation and stress history that affected Meso‐Cenozoic limestone strata in the Monte Nero Anticline during its late Miocene‐Pliocene growth in the Umbria‐Marche Arcuate Ridge (northern Apennines, Italy). In this area an extensive stylolite‐joint/vein network developed during layer‐parallel shortening (LPS), as well as during and after folding. Stress fingerprinting illustrates how stress in the sedimentary strata did build up prior to folding during LPS. The stress regime oscillated between strike slip and compressional during LPS before ultimately becoming strike slip again during late stage fold tightening. Our case study shows that high‐resolution stress fingerprinting is possible and that this novel method can be used to unravel temporal relationships that relate to local variations of regional orogenic stresses. Beyond regional implications, this study validates our approach as a new powerful toolbox to high‐resolution stress fingerprinting in basins and orogens combining joint and vein analysis with sedimentary and tectonic stylolite and calcite twin inversion techniques. Key Points: New combination of stylolites and calcite twins inversion as stress indicator during folding Reconstruction of complex stress regime oscillation during fold growth Use of deep sedimentary stylolite gives high resolution access to local burial history